Physical Fitness in World-Class Shot Put Para Athletes During Six Months of Training: A Longitudinal Case Report - Aedo-Munoz, E (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
The purpose of this longitudinal case report was to assess physical fitness changes in world-class shot put para athletes during six months of training. One male (age: 34.8 years; mass: 96.9 kg; height: 1.79 m; sport class: F42), and one female (age: 45.3 years; mass: 60.1 kg; height: 1.64 m: F54) shot put para-thrower were assessed during a 24-week periodized training program, including strength and power training, throws, and plyometrics. Monthly assessments included competitive shot put throwing performance, the medicine ball throw test, and upper-body maximal strength, while body composition was measured before and after the training period. Shot put throwing performance improved by 10.1% and 1.6% for the male and female athletes, respectively. Similarly, performance in the medicine ball throw test increased by 15.2% and 8.4% for the male and female athletes, respectively. Maximal strength increased by 10.3% (male) and 3.3% (female). Body composition changes included an increased lean mass (2.5%) and reduced sum of six skinfolds (-9.8%) in the male athlete, while the female athlete experienced decreased body mass (-2.5%) and skinfolds (-11.7%). World-class shot put para athletes can improve strength and power through a structured periodized training plan. Monitoring strength and performance indicators monthly effectively tracked training adaptations in elite para athletes.